The Influence of Parenting Styles on Study Discipline - Simanullang, Annisya Rahma; Hasibuan, Ali Daud (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
This research is a quantitative study of the correlational type. The study is motivated by issues related to parenting styles that are connected to children's (students') learning discipline, with parents being a micro factor influencing children's learning discipline. The author conducted research at Mts Negeri Barus to determine whether there is an effect of parenting styles on the learning discipline of seventh-grade students, with a total of 34 students. Thus, the population and sample of this study consist of 34 respondents, as the seventh grade is a phase where, in terms of emotional intelligence, students are better at managing their emotions and involve conscious control to regulate them. The results of the study indicate that children's learning discipline is good. From the correlation table above, it is known that the calculated r value is 0.802 > 0.339 and the sig. value is 0.000 < 0.05, so it can be concluded that there is a positive and significant effect of parenting styles on the learning discipline of seventh-grade students at Mts Negeri Barus, with a perfect or large influence level. The data analysis technique used calculations of the mean, median, mode, and standard deviation with the help of SPSS 20.